2015
DOI: 10.1097/mco.0000000000000227
|View full text |Cite
|
Sign up to set email alerts
|

An update on Curcuma as a functional food in the control of cancer and inflammation

Abstract: The laboratory and the clinical studies until 2011 were summarized in a review published in this journal. An update of the new studies and knowledge from 2011 to March 2015 focuses on new ways to overcome its low bioavailability and data from clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…W., Booth, J., 2004;Daily, Yang, & Park, 2016;EMA, 2017;Ghalaut et al, 2012;Gupta et al, 2013;Khajehdehi et al, 2012;Kuptniratsaikul et al, 2014;Kuttan, Sudheeran, & Josph, 1987;Schaffer, Schaffer, & Bar-Sela, 2015). W., Booth, J., 2004;Daily, Yang, & Park, 2016;EMA, 2017;Ghalaut et al, 2012;Gupta et al, 2013;Khajehdehi et al, 2012;Kuptniratsaikul et al, 2014;Kuttan, Sudheeran, & Josph, 1987;Schaffer, Schaffer, & Bar-Sela, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…W., Booth, J., 2004;Daily, Yang, & Park, 2016;EMA, 2017;Ghalaut et al, 2012;Gupta et al, 2013;Khajehdehi et al, 2012;Kuptniratsaikul et al, 2014;Kuttan, Sudheeran, & Josph, 1987;Schaffer, Schaffer, & Bar-Sela, 2015). W., Booth, J., 2004;Daily, Yang, & Park, 2016;EMA, 2017;Ghalaut et al, 2012;Gupta et al, 2013;Khajehdehi et al, 2012;Kuptniratsaikul et al, 2014;Kuttan, Sudheeran, & Josph, 1987;Schaffer, Schaffer, & Bar-Sela, 2015).…”
mentioning
confidence: 99%
“…R. W., Booth, J., 2004;Daily, Yang, & Park, 2016;EMA, 2017;Ghalaut et al, 2012;Gupta et al, 2013;Khajehdehi et al, 2012;Kuptniratsaikul et al, 2014;Kuttan, Sudheeran, & Josph, 1987;Schaffer, Schaffer, & Bar-Sela, 2015).…”
mentioning
confidence: 99%
“…Free radicals usually attack several cell components, such as the polyunsaturated fatty acid (PUFA), deoxyribonucleic acid (DNA) and proteins (Schaffer et al, 2015). An increase in free radicals causes overproduction of Malondialdehyde (MDA), a final product of polyunsaturated fatty acids peroxidation in cells (Ewing et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological studies of this herb resulted in reports on the antiinflammatory effects of the extract and sesquiterpenes were reported. [47][48][49][50] In our previous studies, we reported the hepatoprotective, vasodilative, and nitric oxide production-inhibitory activities of various sesquiterpenes and curcuminoids isolated from the rhizomes of C. zedoaria cultivated in China. [51][52][53][54][55][56] In our study, the 80% aqueous acetone extract of the dried rhizomes of C. zedoaria cultivated in Thailand (Thai zedoary) 57) was found to inhibit the release of β-hexosaminidase induced by the antigen in sensitized RBL-2H3 cells and ear PCA reactions in mice.…”
Section: Curcuminoidsmentioning
confidence: 99%